(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
Reading academic texts is a fundamental skill for success in higher education, as it enables students to engage with disciplinary knowledge, interpret complex ideas, and develop critical thinking skills. However, many undergraduates experience difficulties in comprehending academic materials. One important factor that supports effective reading is the use of metacognitive reading strategies, which allow learners to plan, monitor, and evaluate their understanding during reading. Although these strategies have been widely studied, variations in their use among different learner groups remain underexplored. One such area concerns gender-based differences in strategy use. This study therefore investigates gender differences in metacognitive reading strategies in academic text processing among Nigerian undergraduates. The study is anchored in Metacognitive Theory (Flavell, 1979) and adopts the Metacognitive Awareness of Reading Strategies Inventory (MARSI) framework (Mokhtari & Reichard, 2002), which categorizes strategies into global, problem-solving, and support strategies. Using a stratified random sampling technique, data were collected from 200 undergraduates (100 males and 100 females) drawn from three Nigerian universities: Nnamdi Azikiwe University, Awka; Imo State University, Owerri; and Tansian University, Umunya. Descriptive statistics were used to identify patterns of strategy use, while independent samples t-tests were conducted to examine gender differences. The findings reveal that students employ all three categories of metacognitive strategies. However, female students reported significantly higher use of global and support strategies than male students, while no significant gender difference was found in problem-solving strategies. The results indicate that gender plays a role in shaping students’ metacognitive engagement with academic texts and suggest the need for more inclusive and strategy-focused reading instruction in Nigerian universities.